Letter (copy) : Criticism of Home - Tewson, Vincent
1938-04-06 038-0146-001 HVT/FC/373. Secretary's. 6th April, 1938. Mr. D. Lewry, The Carshalton & District Basque Children's Committee, 10, Waverley Avenue, Sutton, SURREY. Dear Sir, CRITICISM OF HOME. I have your letter of the 3rd instant in regard to the above matter. It is quite true that I heard certain criticisms of the conduct of the Home and I conveyed these to Miss Arne, Secretary of the National Committee. It so happened, however, that she went down to Carshalton the previous evening and from what she said it did appear that the steps that were being taken as the result of her visit were likely to put right most of the complaints conveyed to me. When I had a talk with Miss Arne it was merely with a view to some official enquiry being made in regard to the correctness or otherwise of the reports. In these matters I am loath to accept reports without full enquiry. I hope, however, that things will soon be proceeding on a more satisfactory basis and that such difficulties as you may have had will gradually be overcome. Yours sincerely, 292/946/38/146(I)